2007
DOI: 10.1124/jpet.107.120444
|View full text |Cite
|
Sign up to set email alerts
|

S-(1,2,2-Trichlorovinyl)-l-cysteine Sulfoxide, a Reactive Metabolite ofS-(1,2,2-Trichlorovinyl)-l-cysteine Formed in Rat Liver and Kidney Microsomes, Is a Potent Nephrotoxicant

Abstract: Previously, we have provided evidence that cytochromes P450 (P450s) and flavin-containing monooxygenases (FMOs) are involved in the oxidation of S-(1,2,2-trichlorovinyl)-L-cysteine (TCVC) in rabbit liver microsomes to yield the reactive metabolite TCVC sulfoxide (TCVCS). Because TCVC is a known nephrotoxic metabolite of tetrachloroethylene, the nephrotoxic potential of TCVCS in rats and TCVCS formation in rat liver and kidney microsomes were investigated. At 5 mM TCVC, rat liver microsomes formed TCVCS at a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…One important limitation of this method, however, is its focus on proximal metabolites of the GSH conjugation pathway and not on some of the more reactive and toxic downstream metabolites such as TCVC sulfoxide (Elfarra and Krause 2007). Still, the method reported herein will be applicable to further toxicokinetic studies of PERC and inform human health assessments of this ubiquitous environmental toxicant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One important limitation of this method, however, is its focus on proximal metabolites of the GSH conjugation pathway and not on some of the more reactive and toxic downstream metabolites such as TCVC sulfoxide (Elfarra and Krause 2007). Still, the method reported herein will be applicable to further toxicokinetic studies of PERC and inform human health assessments of this ubiquitous environmental toxicant.…”
Section: Resultsmentioning
confidence: 99%
“…1,2,2-trichlorovinylthiol can spontaneously form a reactive thioketene which can adduct to DNA and proteins (IARC 2014). PERC metabolites from the GSH conjugation pathway are cytotoxic in vitro (Lash et al 2002, Birner et al 1997, Irving and Elfarra 2013) and nephrotoxic in vivo (Birner et al 1997, Elfarra and Krause 2007). They are also mutagenic (Vamvakas et al 1989b, Vamvakas et al 1989a, Irving and Elfarra 2013).…”
Section: Introductionmentioning
confidence: 99%
“…DCVC can be oxidized by flavin-containing monooxygenases (FMOs) (Ripp et al, 1997; Krause et al, 2003) and TCVC can be oxidized by FMOs or cytochrome P450s (Ripp et al, 1997). DCVCS (Lash et al, 1994) and TCVCS (Elfarra and Krause, 2007) have both been demonstrated to be more nephrotoxic than the precursor cysteine S -conjugates, likely due to their ability to act as direct-acting toxicants through covalent reactions with sulfhydryl-containing molecules. Recently, DCVCS-hemoglobin adducts and cross-links have been detected in rats given DCVC, providing evidence for in vivo metabolism of DCVC to DCVCS (Barshteyn and Elfarra, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The mercapturic acids are cytotoxic in rat renal epithelial cells, and their cytotoxicity is reduced by the -lyase inhibitor (aminooxy)acetic acid, indicating hydrolysis of the mercapturic acids and -lyasecatalyzed bioactivation of the formed cysteine S-conjugates (176); (aminooxy)acetic acid failed to reduce the cytotoxicity of the corresponding mercapturic acid sulfoxides, indicating that they are direct-acting electrophiles. Recent studies show, however, that both FMO and P450 are involved in the sulfoxidation of S-(trichlorovinyl)-L-cysteine (178). (Fluoromethoxy)-1,1,3 The role of vinylic cysteine S-conjugate-derived sulfoxides in the nephrotoxicity and cytotoxicity of cysteine S-conjugates merits further investigation to establish the role of cysteine S-conjugate S-oxidation by FMO or P450 in the nephrotoxicity of vinylic cysteine S-conjugates.…”
Section: Vinylic Sulfoxidesmentioning
confidence: 96%